The Influence Of Peer Group Interaction And Moral Development Toward Aggression Behavior of School-Aged Children In Urban Poor Areas - Yayang Wtri A Djohari; Neti Hernawati (Journal of Child Development Studies, 2018)
This research aimed to analyze the relationship and influence of children and family characteristic,  interaction of peer group, moral development toward agression behavior of  school age chidren in Tegal Lega Village, Middle District of Bogor and Empang Village, South District of Bogor.  Design of this research was cross sectional study. Population of this reserch were family with school-age late childhood or 4-6 class elementery school. The samples consist 100 children and mothers  were chosen by proportional random sampling. The data collected by interview based on questionnaire. Result showed that were significant and negative correlation between moral development with aggression behavior.  Meanwhile, result showed that were significant and negative influence between moral development toward aggression behavior. This research was not found influence between child characteristic and peer group interaction toward aggression behavior.